5-year overall survival after early breast cancer diagnosed during pregnancy: A retrospective case-control multicentre French study. (May 2018) - Ploquin, A.; Pistilli, B.; Tresch, E.; Frenel, J.S.; Lerebours, F.; Lesur, A.; Loustalot, C.; Bachelot, T.; Provansal, M.; Ferrero, J.M.; Coussy, F.; Debled, M.; et al.
Abstract: Background: Breast cancer diagnosed during pregnancy (BCP) is rare, but the prevalence is expected to rise. Long-term follow-up data regarding this clinically challenging condition are scarce. The main objective of this multicentre case-control French study was to compare the survival between pregnant patients and matched controls. Methods: Patients from 27 centres diagnosed between 2000 and 2009 with histologically proven invasive breast cancer occurring during pregnancy were retrospectively included. Controls were matched to BCP patients on age, clinical T stage, hormone receptor, HER2, administration of neo-adjuvant chemotherapy and pathological node involvement in the absence of neo-adjuvant chemotherapy. Five-year overall survival (OS), disease-free survival (DFS) and metastasis-free survival (MFS) rates were estimated using the Kaplan–Meier method. Results: One hundred and eleven BCP patients and 253 controls were included. Median age was 33 and 35 years, respectively. Both populations were managed similarly, except for less frequent sentinel node dissection (p = 0.026) and taxane administration (p = 0.03) among BCP patients. Median follow-up was 7.5 years. Survival rates were similar between both BCP and control patients: 5-year OS rates were 83.1% (95% CI: 74.5–89.0) vs 85.5% (95% CI: 80.4–89.4), respectively, p = 0.31; 5-year DFS rates 60.0% (95% CI: 50.1–68.6) vs 68.5% (95% CI: 62.3–73.9), respectively, p = 0.12 and 5-year MFS rates 71.0% (95% CI: 61.3–78.6) and 74.5% (95% CI: 68.6–79.5), respectively, p = 0.21. Conclusion: Our study showed that the survival outcomes of patients diagnosed with BCP were not significantly different as compared to those of matched non-pregnant controls. A proper management of women diagnosed with BCP is crucial. Highlights: Pregnancy at the time of breast cancer diagnosis was not associated with worse outcomes. According to IHC classification, the prognosis was the same in both groups. Proper management of women diagnosed with breast cancer during pregnancy is crucial.